Ernesta Foldāta vēstule draugiem Latvijā 1999. gada aprīlī - Foldāts, Ernests (My University, 1999)
Ernesta Foldāta vēstule draugiem Latvijā, kurā viņš raksta par savu veselības stāvokli, Venecuēlas slikto ekonomisko stāvokli, neapmierinātību ar jauno prezidentu, Foldātam veltītu bakalaura darbu, ko Daugavpils Pedagoģiskajā Universitātē uzrakstījusi Olga Dubrovska, par iegūtajām atzinībām no Venecuēlas Centrālās Universitātes, doktorantu disertāciju vadīšanu. Drukāts mašīnrakstā uz vienas lapas, ar parakstu labajā apakšējā stūrī. Glabājas Latvijas Universitātes Muzeja Botānikas un mikoloģijas kolekciju krājumā.
Letter from Ernesto Foldat to friends in Latvia, April 1999
Ernesto Foldat's letter to friends in Latvia, in which he writes about his state of health, Venezuela's poor economic situation, dissatisfaction with the new president, a bachelor's thesis dedicated to Foldat written by Olga Dubrovska at Daugavpils Pedagogical University, about recognitions from the Central University of Venezuela, supervision of doctoral dissertations. Typed on one page, with a signature in the lower right corner. Stored in the Museum of the University of Latvia Botanical and Mycological collections.
Keywords: Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Human communication; Ernesto Foldat; korespondence; correspondence; Ekonomiskais stāvoklis - Venecuēla; Economic situation - Venezuela; Research Subject Categories::NATURAL SCIENCES::Biology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science